Behavioral Intention to Adopt Green Banking Technology: The Influence of UTAU and Environmental Concern Factors - Khalifa, Sri Aulia; Wibowo, Mas Wahyu (Journal of Sustainable Economic and Business, 2025)
Objectives: This study examines the influence of UTAUT and environmental concern on behavioral intention and Green Banking Product adoption, focusing on gender differences.Methodology: A survey was conducted using Google Forms with 129 respondents from BCA, BRI, BNI, and Mandiri bank customers in Banten, DKI Jakarta, West Java, Central Java, East Java, and Yogyakarta. The study employs a correlational design with cross-sectional data collection. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used for analysis.Findings: Results show that Facilitating Conditions and Social Influence do not significantly impact behavioral intention. However, gender moderates the relationship between Effort Expectancy and Behavioral Intention, indicating differences between male and female respondents.Conclusion: Certain UTAUT factors may not directly influence behavioral intention, but gender plays a key role in Green Banking adoption. These findings can help banks develop targeted strategies to encourage adoption.